Edukasi Kesehatan dengan Model SECI Berbasis Augmanted Reality Terhadap Self-Care Management dan Kepatuhan Cairan pada Pasien Gagal Ginjal Kronis dengan Hemodialisis - Jamini, Theresia; Chrismilasari, Lucia Andi; Negara, Candra Kusuma; Prawira, Ricky (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of health education using the SECI model based on Augmented Reality (AR) on self-care management and fluid adherence in patients with chronic kidney disease undergoing hemodialysis. The method was a quasi-experimental study with a pretest-posttest approach and a control group design. The results showed a significant increase in self-care management and fluid adherence scores in the intervention group compared to the control group (p < 0.05). In conclusion, education based on the SECI model and Augmented Reality has been proven effective in improving self-management skills and fluid adherence in hemodialysis patients and positively impacting their overall quality of life. Keywords: Augmented Reality, Health Education, Chronic Kidney Disease, Hemodialysis, Fluid Adherence, SECI Model, Self-Care Management